Root and tuber crops for agricultural transformation in Malawi. Project profile. - International Potato Center (International Potato Center, 2019)
Roots and tubers have great potential to support food security and build resilient livelihoods among the poorest and most vulnerable people in Malawi. The Root and tuber crops for agricultural transformation in Malawi (RTC-ACTION Malawi) project aims to boost production and consumption of these crops, thereby supporting the country’s efforts to cut poverty, hunger and malnutrition.